PENGARUH PENGETAHUAN INVESTASI, RISIKO, DAN MODAL MINIMAL TERHADAP MINAT INVESTASI MAHASISWA INSTITUT BISNIS DAN KEUANGAN NITRO MAKASSAR DI PASAR MODAL - Endang Simak Sanggaria; Muspa Muspa; Rosnaini Daga (Jurnal Sains Manajemen Nitro, 2023)
The purpose of this study was to determine the effect of investment knowledge, risk, and minimum capital on investment interest of Nitro Makassar Business and Finance Institute Students. The sample in this study were active students of the Nitro Institute of Business and Finance Makassar who were in the program or had passed the money and capital market course or portfolio theory and investment analysis with a total of 75 respondents. The analysis method used in this research is multiple linear regression analysis. The results of this study indicate that investment knowledge, risk and minimum capital have a positive and significant effect on investment interest.